MORAL VALUES OF MASSACHUSETTS SOCIETY IN THE PURITAN ERA: A STUDY ON NATHANIEL HAWTHORNES THE SCARLET LETTER - Didik Rinan Sumekto (Celt: A Journal of Culture, English Language Teaching & Literature, 2014)
This study aimed at revealing and discussing the life of Arthur Dimmesdale and Hester Prynne as depicted in Nathaniel Hawthornes The Scarlet Letter, which adopted the moral values set in the past nineteenth century Massachusetts society. The research used the historical qualitative method by focusing on empirical facts found in the research site in accordance with the structural society existence in a particular period. Data collection and interpretation technique was applied systematically by explaining and describing the actions and events of the story with facts about the Puritan dogma. The findings showed that the moral values had described the life of Arthur and Hester, as the major character via (1) the satirical outline on the actual world of morality within Massachusetts society; (2) the degree of Puritan morality, hypocrisy, guilt and final painful expiation to Arthur and Hester, to which they had condemned, violated, and led to a consequence of punishment upon their moral hazard, since the law of God and the manmade law treachery were seductively done on behalf of love; and (3) the empirical understanding of the consequence and positive implication of life in struggling for honesty, honor, dignity, strength and endurance